Sikronisasi Peraturan Kode Etik Berpakaian Mahasiswa UINSU Dengan Hukum Al-Qu’ ran - Fara Aprillia Puteri; Ikhtiari Akhiriyah; Syahrul Romadhon; Siti Sahara; Ahmad Rifaldi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Aurat is one of the things that must be considered for a Muslim woman. Allah commands every Muslim woman to cover her aurat as best as possible to avoid unwanted things. The existence of rules made by Allah is none other than to maintain the dignity and safety of a Muslim woman. This article will discuss the dress code in the code of ethics of UIN North Sumatra relating to Quranic verses or propositions. The purpose of this study was to find the relationship between Qur'anic verses or propositions with the dress code of UIN North Sumatra. This study uses literature study research which reviews previous journals and reads several references to find the important points needed by the author in writing this article. The result of this study is that the rules used and applied by UIN North Sumatra regarding the dress of a Muslim woman are very closely related to the verses and hadith in Islam.